Sleep-disordered breathing in C57BL/6J mice with diet-induced obesity. Issue 8 (15th May 2018) - Fleury Curado, Thomaz; Pho, Huy; Berger, Slava; Caballero-Eraso, Candela; Shin, Mi-Kyung; Sennes, Luiz Ubirajara; Pham, Luu; Schwartz, Alan R; Polotsky, Vsevolod Y
Abstract: Obesity leads to sleep-disordered breathing (SDB) manifested by recurrent upper airway obstructions termed obstructive sleep apnea (OSA) and carbon dioxide retention due to hypoventilation. The objective of this work was to characterize breathing during sleep in C57BL6/J mice with diet-induced obesity (DIO). Arterial blood gas was measured in nine obese and nine lean mice during wakefulness. Nine male mice with DIO and six lean male C57BL/6J mice were head mounted with electroencephalogram (EEG) and electromyogram (EMG) electrodes. Sleep recordings were performed in the whole body plethysmography chamber; upper airway obstruction was characterized by the presence of inspiratory flow limitation in which airflow plateaus with increases in inspiratory effort. Obese mice showed significantly lower pH and higher partial pressure of arterial CO2 (PaCO2 ) in arterial blood gas compared to lean mice, 7.35 ± 0.04 versus 7.46 ± 0.06 ( p < 0.001) and 38 ± 8 mm Hg versus 30 ± 5 mm Hg ( p < 0.001). Obese mice had similar levels of minute ventilation to lean mice during sleep and wakefulness, despite higher body weight and temperature, indicating an increase in the metabolic rate and hypoventilation. Obese mice also showed baseline hypoxemia with decreased mean oxyhemoglobin saturation across sleep/wake states. Obese mice had a higher prevalence of flow-limited breathing compared to lean mice during sleep. However, the oxygen desaturation index in lean and obese mice did not differ. We conclude that DIO in mice leads to hypoventilation. Obesity also increases the frequency of inspiratory limited breaths, but it does not translate into progression of OSA.